The Effect of Life Skills Training on Decision-making Skills of Dyscalculic Students - Vashistha, K.C.; Bapte, Aditi (JOURNAL OF INDIAN EDUCATION, 2016)
The objective of the present paper is to examine the efficacy of life skills training on the decision-making skills of dyscalculics at the elementary level. This research is quasi-experimental in nature, based on pre-test and post-test design. Thirty dyscalculic students from the elementary level in Agra city were selected and divided into two equal groups of Experimental (n=15) and Control (n=15). Training sessions on life skills were administered on the Experimental group for a period of one month in their schools. The tools used were (i) Dyscalculic identification scale, (ii) Making decisions in everyday life, and (iii) Life skills training through self-constructed lesson plans. The statistical analysis exhibited that the Experimental group showed a positive enhancement in decision-making skills as compared to the control group of dyscalculic students. The result, thus, inferred that the life skills training can effectively bring about an increment in the decision-making skills of dyscalculic students, which can ameliorate their existing conditions to a certain extent. It also confirms that the provision of life skill-based curricula in these schools caters to the needs of dyscalculic children in a better way by enhancing their calibre to face the world at large.